2013
DOI: 10.1016/j.clml.2013.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Novel Treatment Options for Waldenström Macroglobulinemia

Abstract: Waldenström’s macroglobulinemia first described by Jan Waldenström in 1944 is a lymphoplasmacytic lymphoma characterized by the presence of an immunoglobulin M (IgM) monoclonal gammopathy in the blood and monoclonal small lymphocytes and lymphoplasmacytoid cells in the bone marrow. WM is a rare and indolent disease but remains incurable. In this review we discuss the pathogenesis of Waldenström macroglobulinemia and focus on novel treatment options that target pathways deregulated in this disease. Recent studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…1,2 Median survival is ;8 to 10 years, and the disease varies from one with indolent course to a disease that needs rapid control. [3][4][5] WM cells express CD20 surface antigen; therefore, rituximab has become a key treatment component; however, it is associated with a modest response rate of ;30% and long time to response. [6][7][8] Thus, it is recommended that primary treatment should consist of rituximab-based combinations, to increase response rates and shorten time to response.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Median survival is ;8 to 10 years, and the disease varies from one with indolent course to a disease that needs rapid control. [3][4][5] WM cells express CD20 surface antigen; therefore, rituximab has become a key treatment component; however, it is associated with a modest response rate of ;30% and long time to response. [6][7][8] Thus, it is recommended that primary treatment should consist of rituximab-based combinations, to increase response rates and shorten time to response.…”
Section: Introductionmentioning
confidence: 99%
“…WM is a rare low-grade lymphoproliferative disorder characterized by the presence of monoclonal IgM paraprotein in the serum and lymphoplasmacytic infiltration of the bone marrow [15,16]. Chng et al [17] reported a relatively homogeneous expression profile among the WM cases, indicating that WM was more similar to chronic lymphocytic leukemia than multiple myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) serve as the progenitor for most bone marrow stromal cell populations, including osteoblasts, chondrocytes, fibroblasts, endothelial cells, and myocytes [ 18 ]. In WM, BMSCs have been shown to regulate the proliferation of tumor cells while contributing to increased drug therapy resistance [ 19 ].…”
Section: Tumor Microenvironmentmentioning
confidence: 99%